Evaluating the cooling rate of hot mix asphalt in tropical climate - Abdullah, Mohd Ezree; Abdul Hassan, Norhidayah; Wardati, Wardati; Hainin, Mohd Rosli; Ismail, Norfarah Nadia; Md. Yusoff, Nur Izzi (PENERBIT UTM PRESS, 2016)
This paper aims to investigate the environmental effect on cooling rate and to determine the appropriate time available for compaction (TAC) using laboratory tests. This includes the study parameters, namely solar flux, base and ambient temperatures (daytime and night-time paving) and wind velocity, focusing on hot mix asphalt (HMA) asphalt concrete wearing with 14 mm nominal maximum aggregate size (ACW14) mix type for the wearing course and ACB28 mix type for the binder course. Samples were prepared in slab moulds 30.5 cm × 30.5 cm × 5 cm and compacted using a manually operated steel-roller. Readings were taken by averaging the temperature measurements at the middle and surface of the slabs and a temperature of 160 ºC was used as the mixing temperature. A control sample was prepared for each mix type and tested in the laboratory without the influence of wind velocity and solar flux. It was found that the cooling rate of HMA is significantly affected by environmental factors, thus influencing the TAC. The TAC tends to decrease by 15-50% during windy and night conditions but increases by up to 100% during daytime conditions compared to the control samples.